Mycofactocin Is Associated with Ethanol Metabolism in Mycobacteria - Gopinath Krishnamoorthy; Peggy Kaiser; Laura Lozza; Karin Hahnke; Hans-Joachim Mollenkopf; Stefan H. E. Kaufmann (mBio, 2019)
ABSTRACT Mycofactocin (MFT) belongs to the class of ribosomally synthesized and posttranslationally modified peptides conserved in many Actinobacteria. Mycobacterium tuberculosis assimilates cholesterol during chronic infection, and its in vitro growth in the presence of cholesterol requires most of the MFT biosynthesis genes (mftA, mftB, mftC, mftD, mftE, and mftF), although the reasons for this requirement remain unclear. To identify the function of MFT, we characterized MFT biosynthesis mutants constructed in Mycobacterium smegmatis, M. marinum, and M. tuberculosis. We found that the growth deficit of mft deletion mutants in medium containing cholesterol—a phenotypic basis for gene essentiality prediction—depends on ethanol, a solvent used to solubilize cholesterol. Furthermore, functionality of MFT was strictly required for growth of free-living mycobacteria in ethanol and other primary alcohols. Among other genes encoding predicted MFT-associated dehydrogenases, MSMEG_6242 was indispensable for M. smegmatis ethanol assimilation, suggesting that it is a candidate catalytic interactor with MFT. Despite being a poor growth substrate, ethanol treatment resulted in a reductive cellular state with NADH accumulation in M. tuberculosis. During ethanol treatment, mftC mutant expressed the transcriptional signatures that are characteristic of respirational dysfunction and a redox-imbalanced cellular state. Counterintuitively, there were no differences in cellular bioenergetics and redox parameters in mftC mutant cells treated with ethanol. Therefore, further understanding of the function of MFT in ethanol metabolism is required to identify the cause of growth retardation of MFT mutants in cholesterol. Nevertheless, our results establish the physiological role of MFT and also provide new insights into the specific functions of MFT homologs in other actinobacterial systems. IMPORTANCE Tuberculosis is caused by Mycobacterium tuberculosis, and the increasing emergence of multidrug-resistant strains renders current treatment options ineffective. Although new antimycobacterial drugs are urgently required, their successful development often relies on complete understanding of the metabolic pathways—e.g., cholesterol assimilation—that are critical for persistence and for pathogenesis of M. tuberculosis. In this regard, mycofactocin (MFT) function appears to be important because its biosynthesis genes are predicted to be essential for M. tuberculosis in vitro growth in cholesterol. In determining the metabolic basis of this genetic requirement, our results unexpectedly revealed the essential function of MFT in ethanol metabolism. The metabolic dysfunction thereof was found to affect the mycobacterial growth in cholesterol which is solubilized by ethanol. This knowledge is fundamental in recognizing the bona fide function of MFT, which likely resembles the pyrroloquinoline quinone-dependent ethanol oxidation in acetic acid bacteria exploited for industrial production of vinegar.